Pengelolaan Sumber Daya Pesisir Berkelanjutan Melalui Penerapan Teknologi Berbasis Pengetahuan Lokal - Heni Nopianti; Ika Pasca Himawati (Indonesian Center for Religion and Society Studies (InTReSt), 2022)
The research aims to describe the management of coastal marine resources of the people of Kungkai Baru Village, Seluma Regency, Bengkulu-Indonesia Province, in the river estuary area with nature reserve status. Research methods apply an exploratory qualitative approach to explore the focus of the problem. The data was obtained through a process of non-participant observation and in-depth interviews. Informants are determined based on purposive sampling techniques so that selected fishers, indigenous figures, and community leaders who have lived for a long time and live in Kungkai Baru Village. Research data analysis adopts Miles and Huberman's Interactive Model, including data reduction, presentation, and inference. Research produces information that the management of coastal marine resources in the Kungkai estuary is carried out using non-machined fishing gear such as nets, waring, canoes, and memorable fishing gear called belik. This study found that local knowledge-based fishing gear used by anglers is a form of sustainable management of coastal marine resources in Muara Kungkai.